CD4 T-Cell Subsets in Malaria: TH1/TH2 Revisited - Perez-Mazliah, Damian; Langhorne, Jean (Frontiers in Immunology, 2015)
CD4+ T cells have been shown to play a central role in immune control of infection with Plasmodium parasites. At the erythrocytic stage of infection, IFN-γ production by CD4+ T cells and CD4+ T-cell help for the B-cell response are required for control and elimination of infected red blood cells. CD4+ T cells are also important for controlling Plasmodium pre-erythrocytic stages through the activation of parasite-specific CD8+ T cells. However, excessive inflammatory responses triggered by the infection have been shown to drive pathology. Early classical experiments demonstrated a biphasic CD4+ T-cell response against erythrocytic stages in mice, in which T helper (Th)1 and antibody helper CD4+ T cells appear sequentially during a primary infection. While IFN-γ-producing Th1 cells do play a role in controlling acute infections, and they contribute to acute erythrocytic-stage pathology, it became apparent that a classical Th2 response producing IL-4 is not a critical feature of the CD4+ T cell response during the chronic phase of infection. Rather, effective CD4+ T-cell help for B cells, which can occur in the absence of IL-4, is required to control chronic parasitemia. IL-10, important to counterbalance inflammation and associated with protection from inflammatory-mediated severe malaria in both humans and experimental models, was originally considered be produced by CD4+ Th2 cells during infection. We review the interpretations of CD4+ T cell responses during Plasmodium infection, proposed under the original Th1/Th2 paradigm, in light of more recent advances, including the identification of multifunctional T cells such as Th1 cells co-expressing IFN-γ and IL-10, the identification of follicular helper T cells (Tfh) as the predominant CD4+ T helper subset for B cells, and the recognition of inherent plasticity in the fates of different CD4+ T cells.